Sport Trails - Greuel, Duane (University of Wisconsin-Stevens Point, 1979)
This guide is designed to introduce the concept and planning of sport trails to park managers and recreation planners in the United States. It is presented in three parts and includes: 1) background information on sport trails; 2) procedures for establishing, operating, maintaining, and financing sport trails, and; 3) how to develop a sport trail plan. Detailed dimension and design features are presented to help illustrate concepts and principles. European sport trail concepts and fundamental information about hiking trails were integrated to establish planning and construction guidelines. Suggestions on how to design trails are presented with illustrations. Part III suggests planning procedures to follow, relates to suggested designs, and utilizes an integrated approach to sport trail planning.